STRUKTUR HEMIRING - Noviliani Noviliani; Saman Abdurrahman; Na'imah Hijriati (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2021)
Hemiring is a non-empty set which is equipped with the addition operation